Trauma and Growth: Impact of AIDS Activism - Judith G. Rabkin; Martin C. McElhiney; Mark Harrington; Tim Horn (AIDS Research and Treatment)
Introduction. Our goal was to assess the long-term impact of AIDS activism of ACT UP/New York on the current adjustment of those who were members during its peak years (1987–1992), including assessment of trauma sequelae as well as posttraumatic growth. Methods. A 90-minute semistructured interview and 6 validated self-report scales were administered. We relied on purposive and snowball sampling to recruit potential participants. Areas covered include demographics, ACT UP participation, and psychiatric problems. Self-report scales provided approximate diagnoses of PTSD and depression, as well as coping, optimism, and related concepts. Results. Participants included 102 men (40% HIV-positive) and 23 women. Seventeen percent reported current symptoms suggesting PTSD, slightly above the range in general population studies. Symptoms consistent with depression were reported by 8% overall, with higher rates for HIV+ men. Enhanced sense of self, belief in change, and empowerment were reported by 93% of respondents, independent of concurrent PTSD or depression. Conclusions. Twenty-eight years later, ACT UP study participants recall their activist days during the AIDS epidemic as the peak experience of their lives. While some continue to have symptoms of stress and depression, most found that their activism has enriched their subsequent lives.